Gender politics and Victorian literary representation of the body: a distant reading of the body in Charles Dickens’s works - Houliang Chen; Qianwen Xu (Humanities & Social Sciences Communications, 2024)
Abstract This paper analyses the nineteenth-century discourse around the human body. It examines two corpora: Charles Dickens’s works and contemporary writings. In both contexts, the body is observed through a detailed focus on its individual parts. This study employs a corpus-driven approach to investigate the vocabulary used to describe the body in these two corpora, providing complementary explanations to traditional close reading methods. The findings indicate that Victorian authors, including Dickens, tend to use nouns associated with time and space when representing the body, while also placing significant emphasis on codes of etiquette in the depiction of its physical actions. In Dickens’s corpus, nouns related to the body are influenced by gender ideology. Furthermore, a gender-based sub-corpus analysis, particularly focusing on verbs, highlights the disparities in agency between male and female bodies.